برنامج أنشطة فنية ويدوية في تنمية بعض مهارات إعادة تدوير مخلفات البيئة لطفل الروضة ضعيف السمع - سلطوح، فاطمة صبحي عفيفي السيد (جامعة بني سويف - كلية التربية للطفولة المبكرة, 2022)
هدف البحث الحالي إلى التعرف على مدى إمكانية تنمية بعض مهارات إعادة تدوير مخلفات البيئة لطفل الروضة ضعيف السمع، وذلك من خلال تصميم بعض الأنشطة التربوية التي تقوم على الأنشطة الفنية واليدوية كأحد استراتيجيات تعليم وتعلم الطفل في تنمية بعض مهارات إعادة تدوير مخلفات البيئة لطفل الروضة ضعيف السمع، واشتملت عينة البحث على (٢٥) طفلا وطفلة الذين تتراوح أعمارهم بين (5-6) سنوات، مجموعة استطلاعية وعددها (١٤) طفلا وطفلة، ومجموعة تجريبية وعددها (١١) طفلا وطفلة، واستخدم البحث المنهج شبه التجريبي، وكانت الأدوات عبارة عن قائمة بمهارات إعادة تدوير مخلفات البيئة لطفل الروضة ضعيف السمع (إعداد الباحثة)، مقياس مهارات إعادة تدوير مخلفات البيئة المصور لطفل الروضة ضعيف السمع (إعداد الباحثة)، بطاقة ملاحظة الأداء المهارى لإعادة تدوير مخلفات البيئة لطفل الروضة ضعيف السمع (إعداد الباحثة)، برنامج الأنشطة الفنية واليدوية في تنمية بعض مهارات إعادة تدوير مخلفات البيئة لطفل الروضة ضعيف السمع (إعداد الباحثة)، وقد أسفرت نتائج البحث الحالي إلى فعالية البرنامج القائم على الأنشطة الفنية واليدوية في تنمية مهارات إعادة تدوير مخلفات البيئة لطفل الروضة ضعيف السمع. The aim of the current research is to identify the possibility of developing some skills of environmental waste recycling for the hearing-impaired kindergarten child, by designing some educational activities that are based on artistic and manual activities as one of the child’s teaching and learning strategies in developing some skills of recycling environmental waste for the hearing-impaired kindergarten child. The research sample included (25) boys and girls between the ages of (5-6) years, an exploratory group of (14) boys and girls, and an experimental group of (11) boys and girls, and the research used the quasi-experimental method. The tools consisted of a list of environmental waste recycling skills for the hearing-impaired kindergarten child (prepared by the researcher), a scale of skills for recycling environmental waste illustrated for the hearing-impaired kindergarten child (prepared by the researcher), a note card for the skill performance of environmental waste recycling for the hearing-impaired kindergarten child (prepared by the researcher), The program of artistic and manual activities in developing some skills of recycling environmental waste for the hearing-impaired kindergarten child (prepared by the researcher). The results of the current research showed the effectiveness of the program based on artistic and manual activities in developing the skills of recycling environmental waste for the hearing-impaired kindergarten child.
Keywords: الأنشطة الفنية -- التربية البيئية -- أطفال الروضة -- الاضطرابات السمعية